China’s Belt and Road rail freight transport corridors – the economic geography of underdevelopment - Kenderdine, Tristan; Bucsky Péter (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
Traffic volumes between China, Europe and Central Asia through China’s ‘CR Express’ intercontinental rail freight system remain intransparent. We sought new methods of data collection to better understand the significance of this novel trans-Eurasian transport mode. Cumulative causation economic theory can explain how positive industrial development can occur in both linear transport corridors and industrial cluster development in node cities. However on current economic metrics, it is difficult to accept the China narrative of structurally transformative economic development resulting from the intercontinental rail system policy. This paper expresses doubt as to the underlying institutional factors behind the intercontinental rail system being developed by China and its surrounding Eurasian transport policy. We detail the economic theory underpinning the development of the ‘CR Express’ policy through examination of China central level transport policy sources and their horizontal integration with other central-level spatial planning policies, and we examine the deployment of China’s model of intercontinental rail development in the ‘Middle Corridor’ between the Kazakhstan border and Eastern European ports. Both theory and practice point to supply-side development of greater containerised transport capacity resulting in complementarity-driven economic growth clusters. However, without adequate demand, industrial investment in Eurasian clusters, or transparent statistics with which to gauge either the rail freight logistics development or the economic development spill-over effects, we expect to find the initial practical economic results in the Eurasian economies underwhelming. We argue that China’s Eurasian transport policies are not multifaceted enough to result in future growth.